2017
DOI: 10.1111/pace.13060
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Performance of Magnetic Resonance Imaging Conditional and Nonconditional Cardiac Implantable Electronic Devices

Abstract: 1.5 T MRI scanning in patients with MRI conditional and non-MRI conditional cardiac devices was performed with similar, low clinical risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…Furthermore, magnetic resonance imaging (MRI) conditional lead design offers an additional safety benefit, as MRI scanning is now the imaging modality of choice for many neurological and musculoskeletal conditions. In the past, implanted cardiac devices, including pacemakers and implanted cardioverter‐defibrillators, have been contraindicated in MRI scanners, but recent studies and medical societies in both Europe and the United States have suggested that select patients may be safely scanned . Potential adverse effects of an MRI scanner on pacemaker function, such as tissue heating at the lead tip resulting in failure of capture and induced arrhythmias due to unintended cardiac stimulation, remain, however, an ongoing concern .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, magnetic resonance imaging (MRI) conditional lead design offers an additional safety benefit, as MRI scanning is now the imaging modality of choice for many neurological and musculoskeletal conditions. In the past, implanted cardiac devices, including pacemakers and implanted cardioverter‐defibrillators, have been contraindicated in MRI scanners, but recent studies and medical societies in both Europe and the United States have suggested that select patients may be safely scanned . Potential adverse effects of an MRI scanner on pacemaker function, such as tissue heating at the lead tip resulting in failure of capture and induced arrhythmias due to unintended cardiac stimulation, remain, however, an ongoing concern .…”
Section: Introductionmentioning
confidence: 99%
“…While Shah et al. saw no power‐on‐resets in their relatively small series presented in this issue, the six power‐on‐resets reported and one ICD replacement required after MRI in MagnaSafe (a far larger series of 1500 off‐label MRIs) may somewhat temper the enthusiasm for implanting non‐MR‐conditional devices . As noted in a recent review, “The greatest potential risk is that of power‐on reset in pacemaker dependent patients, which may change the programmed mode from asynchronous to synchronous, permitting oversensing of CMR signals and inhibition of pacing output.”…”
mentioning
confidence: 97%
“…In this issue of PACE, Emory University reports their experience of both magnetic resonance (MR) imaging (MRI) of non‐MRI‐conditional devices (often called, “legacy devices” or “off‐label MRI”) and MRI‐conditional devices . Using the metric that any difference in outcomes of off‐and on‐label MRI only be considered relevant if “clinically actionable,” Shah et al.…”
mentioning
confidence: 99%
See 2 more Smart Citations